Expanding the phenotype in argininosuccinic aciduria: need for new therapies. Issue 3 (1st March 2017) - Baruteau, Julien; Jameson, Elisabeth; Morris, Andrew A.; Chakrapani, Anupam; Santra, Saikat; Vijay, Suresh; Kocadag, Huriye; Beesley, Clare E.; Grunewald, Stephanie; Murphy, Elaine; Cleary, Maureen; Mundy, Helen; et al.
Abstract: Objectives: This UK‐wide study defines the natural history of argininosuccinic aciduria and compares long‐term neurological outcomes in patients presenting clinically or treated prospectively from birth with ammonia‐lowering drugs. Methods: Retrospective analysis of medical records prior to March 2013, then prospective analysis until December 2015. Blinded review of brain MRIs. ASL genotyping. Results: Fifty‐six patients were defined as early‐onset ( n  = 23) if symptomatic < 28 days of age, late‐onset ( n  = 23) if symptomatic later, or selectively screened perinatally due to a familial proband ( n  = 10). The median follow‐up was 12.4 years (range 0–53). Long‐term outcomes in all groups showed a similar neurological phenotype including developmental delay (48/52), epilepsy (24/52), ataxia (9/52), myopathy‐like symptoms (6/52) and abnormal neuroimaging (12/21). Neuroimaging findings included parenchymal infarcts (4/21), focal white matter hyperintensity (4/21), cortical or cerebral atrophy (4/21), nodular heterotopia (2/21) and reduced creatine levels in white matter (4/4). 4/21 adult patients went to mainstream school without the need of additional educational support and 1/21 lives independently. Early‐onset patients had more severe involvement of visceral organs including liver, kidney and gut. All early‐onset and half of late‐onset patients presented with hyperammonaemia. Screened patients had normal ammonia at birth and received treatment preventing severe hyperammonaemia. ASL was sequenced ( n  = 19) and 20 mutations were found. Plasma argininosuccinate was higher in early‐onset compared to late‐onset patients. Conclusions: Our study further defines the natural history of argininosuccinic aciduria and genotype–phenotype correlations. The neurological phenotype does not correlate with the severity of hyperammonaemia and plasma argininosuccinic acid levels. The disturbance in nitric oxide synthesis may be a contributor to the neurological disease. Clinical trials providing nitric oxide to the brain merit consideration.